Analysis of the iron profile and the incidence of iron deficiency anemia in the third-trimester pregnant women in the coendemic areas of Bengkulu City, Indonesia - Mohammad Zulkarnain; Rizka Muliani; Rico Januar Sitorus; Nurlaili Nurlaili (AOSIS, 2019)
Pregnant women are at risk for iron deficiency anemia especially pregnant women in malaria-endemic areas. This study aimed to analyze the profile of iron in the third trimester pregnant women with iron deficiency anemia in co-endemic area of Bengkulu city. This study was cross-sectional study with a total sample of 66 pregnant women who met the inclusion criteria. Examination profile of iron in pregnant women is done by taking blood specimen through the vena cubity. Profile iron includes examination sTfR levels, hepcidin, transferrin were examined by ELISA. Determination of iron deficiency anemia is based on the results of Hb, serum iron and TIBC. The results showed 39.4% of pregnant women experience iron deficiency anemia. There is an average difference between hepcidin levels with the incidence of iron deficiency anemia (p-value 0.031). Based on binary logistic regression analysis profile iron with irondeficiency anemia in pregnant women, hepcidin levels are predictors factors on the incidence of iron deficiency anemia (p-value 0.000, 95% CI .296-.709).